Transitioning Vocational Education and Training in Africa : A Social Skills Ecosystem Perspective /: A Social Skills Ecosystem Perspective. (2023) - McGrath, Simon; Openjuru Ladaah, George; Lotz-Sisitka, Heila; Allais, Stephanie; Zeelen, Jacques; Wedekind, Volker; Ramsarup, Presha; Monk, David; Metelerkamp, Luke; Russon, Jo-Anna
No abstract available